Career of Evil : Cormoran Strike #3 - Galbraith, Robert; Glenister, Robert (New York, NY : Hachette Audio, 2015)
When a woman's severed leg is delivered to Robin Ellacott, her boss, private detective Cormoran Strike, looks into his past to determine who is responsible.
Title from container.
Read by Robert Glenister.
Keywords: Private investigators -- England -- London -- Fiction; Man-woman relationships -- Fiction; Mystery fiction; Suspense fiction; Audiobooks